An Interview with Emily Apter. - Bertacco, Simona (CR: The New Centennial Review)
An interview with author and professor of French and Comparative Literature Emily Apter is presented. Topics covered include Apter's interest in untranslatability, her views with regards to equality versus equivalence, and the impact of the politics of class inequality to translational economies. Apter also talks about the postcolonial politics of translational inequality, critical translational humanities, and Angolophone monolingualism.